RAPD genomic fingerprinting differentiates Thiobacillus ferrooxidans strains - Novo, MTM; DeSouza, A. P.; Garcia, O.; Ottoboni, LMM (Gustav Fischer Verlag, 1996)
The PCR-based technique, involving the random amplification of polymorphic DNA (RAPD), was optimized and used for assessing genomic variability among eight Thiobacillus ferrooxidans strains. RAPD fingerprints presented variation for the thirty primers used, giving a total of 269 polymorphic bands. Similarity coefficients between the strains were calculated, and UPGMA cluster analysis was used to generate a dendrogram showing relationships among them. Most primers divided T. ferrooxidans strains in two distinct groups - Group 1: S, SSP, V3, AMF and Group 2: CMV, FG-460, I-35, LR. We observed that the T. ferrooxidans strains used in this work have a high degree of genomic diversity and that RAPD is a powerful method to differentiate them.
Keywords: Thiobacillus ferrooxidans, RAPD; genomic fingerprinting; differentiation; genomic; polymorphism